Optimasi Pemanfaatan Existing Hot Oil System dari Train Sebelumnya Untuk Menujang Proses Pemanasan Medium Pada Train Baru di Kilang Pengolahan Gas X - Dona Novita Umar; Eva Fathul Karamah (Prosiding TAU SNARS-TEK Seminar Nasional Rekayasa dan Teknologi, 2019)
The main processes at the gas processing plant are separation between gas, condensate and water, separation of acid gas (CO2 and H2S), drying of gas and decreasing of Dew point gas. To support the main process, gas processing plants also need utilities such as electricity, heating, gas fuel processing, nitrogen production, water treatment and air treatment. What is discussed in this research is the heating facility for Reboiler. This heating facility is called a hot oil system. The gas processing plant X currently has 2 trains with a design capacity of 310 MMSCFD gas capacity and a condensate capacity design of 13,500 BPD while actual feed gas is higher 352 MMSCFD. The design of the separation of CO2 acid gas is 5% mol and H2S 1000 ppm while the actual concentration of acid in the feed gas is lower, CO2 2% mol and H2S 700 ppm and. Furthermore, in the near future field X will be developed with the addition of gas production of 95 MMSCFD which is planned to be facilitated by the construction of a new train (Train 3). Normally a gas processing train will be equipped with all its supporting facilities, but this research will examine how to optimize the addition of Train 3 by optimizing the utilization of the heating system by existing hot oil system from trains 1 and 2, due to the heat duty capacity of the existing hot oil system is estimated to be excessive and can still facilitate the heating needs of Train 3. The goal will be to save investment costs if this optimization is successfully implemented.